Influence of Bruxism In Children Visiting A University Dental Hospital - A Retrospective Study - N, NOORUL ANEESA.; RAMAKRISHNAN, MAHESH (The journal of contemporary issues in business and government, 2021)
Sleep bruxism is classified as a movement disorder related to sleep. Despite a function is characterised by non-functional teeth contact, manifesting by grinding or tension of teeth. It is not a disease, but when exacerbated may lead to an imbalance of the stomatognathic System. Several therapeutic modalities have been suggested, but there is no consensus about the most efficient. The aim of the study was to access the various symptoms of bruxism in children. The study was based on the date of patients reported to the Department of Pediatric & Preventive Dentistry in a private Dental Hospital, India. The data was obtained from analysing the patient reports for the time frame of June 2019 and March 2020. Various symptoms were diagnosed among which prevalence of pain in tooth and sensitivity was the most common when compared to other symptoms. The study reveals that sensitivity is the most common symptom among the children having bruxism.